HYPERTENSION TREATMENT ADHERENCE AND ASSOCIATED FACTORS AMONG POSTOPERATIVE OPHTHALMIC PATIENTS AT HO CHI MINH CITY EYE HOSPITAL FROM JANUARY TO MARCH 2026 (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of hypertension treatment adherence and analyze associated factors among patients following ophthalmic surgery at Ho Chi Minh City Eye Hospital from January to March 2026.Methods: A cross-sectional descriptive study was conducted on 385 postoperative ophthalmic patients with hypertension. Medication adherence was assessed using the 8-item Morisky Medication Adherence Scale (MMAS-8); patients were considered adherent with an MMAS-8 score ≥ 6. General treatment adherence was defined as the simultaneous fulfillment of four criteria: medication adherence, home blood pressure monitoring, lifestyle modification, and regular follow-up appointments. The association between various factors and treatment adherence was analyzed using Odds Ratios (OR) and 95% Confidence Intervals (95% CI), with significance set at p < 0.05.Results: The rates of adherence were 57.40% for medication, 62.08% for home blood pressure monitoring, 81.82% for lifestyle modification, and 69.61% for scheduled follow-up visits. The overall treatment adherence rate was 38.70%. Statistically significant factors associated with treatment adherence included age group, place of residence, health insurance status, and duration of hypertension.Conclusions: Hypertension treatment adherence among postoperative ophthalmic patients remains low, particularly when evaluated by comprehensive general adherence criteria. Enhanced postoperative support measures are necessary to improve medication adherence, blood pressure monitoring, lifestyle modifications, and follow-up compliance in this patient population.
Keywords: hypertension, treatment adherence, Morisky-8, postoperative ophthalmic patients, associated factors.